Behavioural Analysis of L Shaped RC Columns Using Non-Dimensional Interaction Diagrams by Classical Layer Decomposition Method - ., Sushmitha; shetty, shanmukha; shetty, sabhyath (International Journal of Engineering and Technology, 2018)
The use of rectangular and circular column sections in the construction field are very common and it very easy to analyze and design of these types of column sections. For the design of these column sections load and moment interaction curves are available in sp-16 1980, but for the design of L-shaped column section, the load and moment interaction curves are not available in this code book. The use of L-shaped column in the construction field increases the load carrying capacity of the column. This paper contains the work carried out about the development of load moment interaction curve for L-shaped column section. Â Â